Numerical Finite Element Modelling and Simplified Analytical Methodology for the Structural Analysis of Wound Rotors in Electric Motors - Saverio Giulio Barbieri; Sara Mantovani; Valerio Mangeruga (Engineering Proceedings)
Wound rotor electric motors offer low production costs and environmental sustainability, making them preferable over rare-earth-based motors, particularly at low speeds. However, in automotive applications, the demand for higher specific powers and rotational speeds increases the structural challenges for wound rotors. While commercial Finite Element simulations integrate structural and electromagnetic needs, they could not immediately highlight the influence of single parameters on rotor stress. This paper introduces a simplified analytical methodology for the structural analysis of wound rotors, validated against Finite Element simulations, showing strong agreement. This approach is particularly useful during the early design stages for guiding preliminary geometry definitions.